Comparison of Efficacy and Complications Among Various Spacer Grafts in the Treatment of Lower Eyelid Retraction: A Systematic Review. (3rd March 2017) - Park, Eugene; Lewis, Kevin; Alghoul, Mohammed S
Abstract: Background: Lower eyelid retraction is a difficult problem to treat, but it is a prevalent condition and a common complication of blepharoplasty. The use of spacer grafts to increase eyelid height and improve symptoms has been described for a long time, but the optimal choice of spacer graft material is unknown. Objectives: The authors reviewed the currently available evidence to determine the best available spacer graft material in terms of efficacy and complications. Methods: A systematic review of all available literature published between 1985 and the present was performed using the Pubmed, Ovid MEDLINE, and Cochrane library databases. Inclusion criteria were that the studies contain original content assessing the treatment of lower eyelid retraction in humans using a spacer graft and provide quantitative outcomes data. Results: One hundred and twelve articles were reviewed following an initial screen using titles, and 19 articles were chosen for inclusion in this systematic review. Analysis of these articles revealed no spacer graft material that is clearly superior to others. Conclusions: Due to a lack of high quality evidence, this review did not reveal one spacer graft material that is clearly superior to others. However, a narrative summary of the available evidence reveals unique sets of advantages and disadvantages associated with the various materials currently available. Further research in the form of well-designed studies will be necessary to further clarify advantages of certain spacer graft materials over others. Level of Evidence: 3: